Georgia off the beaten path® : a guide to unique places - McDonald, Janice (Off the beaten path series., 2016)
Whether you're a visitor or a local looking for something different, Georgia Off the Beaten Path shows you the Peach State with new perspectives on timeless destinations and introduces you to those you never knew existed--from the best in local dining to quirky cultural tidbits to hidden attractions, unique finds, and unusual locales. So if you've "been there, done that" one too many times, get off the main road and venture Off the Beaten Path